The Effect of Band Resistance Training on Scythe Speed in Male Athletes of Patbanbu Pencak Silat College - Setiawan, Yogi; Ihsan, Nurul; Zein, Sharah Harmanda (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Studi Purpose This study discusses the low kick speed in male athletes of the Patbanbu pencak silat school in carrying out the sickle kick which results in the kick being successfully avoided, captured, resulting in falls and landslide points for the opponent. The factor that causes the weakness of the ability of the sickle kick, is the speed of the leg muscles. A form of exercise that can increase the speed of leg muscles is resistance band training. Method This research is a type of pseudo-experimental research. The study population was 11 pencak silat college athletes. Sampling was done using purposive sampling techniques with a sample of 7 male athletes. The data analysis technique used the T test. This study was conducted 16 times. The exercises are given in the form of resistance band exercises. The hypothesis proposed in this study is that there is a significant influence of exercise on the speed of the sickle kick. Results of the analysis were that there was a significant influence on resistance band training on the increase in the speed of the crescent kick of Patbanbu pencak silat school athletes in Padang City, obtained a tcount value (5.620) > ttable (2.015) at a significant level of α = 0.05. Therefore, Conclusion it can be concluded that Resistance Band training can provide significant results on sickle speed in male athletes of the Patbanbu pencak silat college, North Padang District, Padang City.